Promote pa more! promoting maintenance and control of hypertension among patients in Barangay Galicia II, Mendez, Cavite - Balbedina, Janine Marie B.; Esparagosa, Jan Petros J.; Gutierrez, Meliz Iren Kaye R.; Tinaja, Charlene J.; Zaño, Basil John Fitzgerald P.; Yanga-Mabunga, Maria Susan T. (Manila College of Public Health, University of the Philippines Manila, 2017)
Galicia II is a barangay located in the fourth-class Municipality of Mendez, Cavite, with a total population of 2,092, and a total of 348 households. The Barangay Health Station (BHS) personnel consists of the Barangay Nurse, and four Barangay Health Workers (BHWs), with a BHW:household ratio of 1:87.

In 2016, acute upper respiratory tract infection was the leading cause of morbidity while chronic obstructive pulmonary disease (COPD) was the leading cause of mortality. Other leading causes of morbidity are mostly infectious in nature. Conversely, majority of the other leading causes of mortality are lifestyle diseases.

No maternal and infant deaths were recorded from 2014 to 2016. However, performance indicators such as supplementations and contraceptive distribution is low. Low utilization of monthly maintenance and control programs for hypertensive patients have been noted. Low case detection rate was also observed in the barangay.

Upon observation, an increasing trend for underage smoking was also observed in the barangay, although no baseline data on the actual prevalence exists.

From the problems identified and based on a set of parameters, the proponents identified low utilization of health services for the maintenance and control of hypertension as the main health problem in Barangay Galicia II.

As such, the proponents decided to implement "PROMOTE PA MORE! Promoting Maintenance and Control of Hypertension among Patients in Barangay Galicia II, Mendez, Cavite". The project aims to promote the utilization of maintenance and control programs for hypertension among hypertensive patients in the barangay, specifically to acquire information regarding the health seeking behavior of hypertensive patients, and educate/inform patients about hypertension and hypertensive programs.

Three prevailing themes were observed in the implementation of the project, namely: Education needs assessment, methodological approach to development of information, education, and communication (IEC) materials, and community engagement.

Focus group discussions (FGDs) and interviews among patients were conducted to assess their knowledge about hypertension and determine their health-seeking behaviour. From this, the main factors affecting service utilization were found out, and the existing gaps on the knowledge and the presence of misconceptions about hypertension were determined. Based from the results, the proponents, along with the barangay health officials and municipal health officer, developed four IEC materials.

The IEC materials focused on addressing key issues from the education needs assessment was developed. Three types of IEC materials were created: Posters, a Calendar, and a Flip Chart. Two posters were created which present information on the symptoms of hypertension, and proper diet for hypertensive patients. A calendar was also created which focuses mainly on encouraging and reminding patients to claim their free medicines at the BHS, highlighting the dates of the monthly drug dispensing, and delivering different messages for the control of hypertension. Lastly, a flip chart which contains information regarding hypertension was also developed, which shall be used by the BHS personnel for future health education sessions with the patients. This also includes a script which was developed during a workshop with the BHWs.

As part of the community engagement, the workshop with the BHWs was conducted wherein they were given the opportunity to stylize their own scripts for the distribution of calendars and the utilization of flipchart, given that they adhere to the advised points to be emphasized. Return demonstrations were done to assure this.

The BHWs deemed the flipcharts and calendars useful for their health education. Also, the Barangay Nurse considers the production of IEC materials as a step closer to the establishment of the barangay's health club. Moreover, the Barangay Captain asserted that the cost for printing the calendar sheets for the next two years will be taken from the barangay's health budget. Finally, the Municipal Health Officer (MHO) was interested in widening the scope of the IEC materials produced.

For the improvement and continuing of the project, the group recommends the conduction of a more in-depth training for the BHWs regarding hypertension, the production of more durable materials, the involvement of the patients' families in the programs, and that the BHS and RHU review the data collected from the FGDs and interviews for the formulation of other interventions for problems not addressed by the project.
Includes references and annexes.
Report
Keywords: Hypertension -- Prevention -- Case studies. -- Philippines -- Cavite .; Community health services -- Case studies. -- Philippines -- Cavite .; Health promotion -- Case studies. -- Philippines -- Cavite .; Patient education -- Community health -- Philippines -- Cavite; Cavite (Philippines) -- Health and hygiene; Mendez (Cavite, Philippines) -- Health and hygiene